Strategi Pemasaran Pariwisata melalui Influencer Marketing - Donny Juliandri Prihadi; Arief Nuryana; Eva Desembrianita; Basnendar Herry Prilosadoso; Muhammad Sabir (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to determine the effectiveness of tourism marketing strategies through influencer marketing. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are that influencer marketing is a powerful tourism marketing strategy in improving tourism image, building trust and credibility in tourism, reaching the right target audience, making tourism the center of attention, increasing trust, increasing engagement and conversion, strengthening social proof, increasing ROI (Return on Investment). In addition, influencer marketing is also an effective strategy in tourism marketing if done correctly. By determining campaign objectives, choosing the right influencers, determining the type of collaboration, creating interesting content, and measuring the success of the campaign. This can increase the attractiveness of tourist destinations and attract more tourists.